An Efficient Model for Smart Home by the Virtualization of Wireless Sensor Network. (20th February 2013) - Islam, Md. Motaharul; Lee, Jun Hyuk; Huh, Eui-Nam
Wireless sensor networks (WSNs) are gaining tremendous importance thanks to their broad range of commercial applications. Out of the contemporary fields of research in WSNs, the virtualization of wireless sensor network (VSN) is a brand new research approach. In this age of economic recession, this state-of-the-art technology can provide the opportunity to build an economic business model for application area such as smart home. Building smart home is a big challenge for worldwide increasing elderly populations which are the largest demographic group of developed countries. In this paper, we propose a VSN based business model for implementing smart home for the rapidly growing elderly populations of the world in a cost-effective way. We also propose the virtualization architecture of fully functional sensor node known as sensor gateway router and mathematical model for the embedding of VSN node and link to the physical sensor node and links. Finally, we have implemented and evaluated the sensor virtualization scheme in embedded Linux environment. The evaluation method shows that the virtualization of sensor network technology reduces the overall cost and complexity significantly for the implementation of smart home.